2005
DOI: 10.1007/s00421-005-1328-1
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of head and trunk accelerations during walking

Abstract: The purpose of this study was to investigate the relationship between oscillatory dynamics of the head and trunk in each plane of motion during walking. Head and trunk accelerations of ten healthy subjects (age: 23 +/- 4 years) were measured in the vertical (VT), anterior-posterior (AP) and mediolateral (ML) directions using a pair of tri-axial accelerometers. All subjects performed five walking trials along a level 20 m walkway at their preferred gait velocity (1.30 +/- 0.15 m s(-1)). Acceleration data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 34 publications
10
76
0
Order By: Relevance
“…In young healthy adults, the oscillations of the upper body during level walking are characterised by an attenuation of the linear acceleration going up from pelvis-to-head level [1][2][3][4]. This attenuation can be read as a control strategy put into place to compensate for the perturbation generated by the lower body movements to preserve the head stability and hence improve walking balance [5].…”
Section: Introductionmentioning
confidence: 99%
“…In young healthy adults, the oscillations of the upper body during level walking are characterised by an attenuation of the linear acceleration going up from pelvis-to-head level [1][2][3][4]. This attenuation can be read as a control strategy put into place to compensate for the perturbation generated by the lower body movements to preserve the head stability and hence improve walking balance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hausdorff et al [11] measured temporal characteristics of gait using stride time variability and swing time variability as markers of impaired control, arhythmicity, and unsteadiness. Variability in the acceleration of the pelvis, trunk or head have also been shown to offer information related to balance control during walking [12][13][14]. Recently, studies using body-worn sensors have suggested that interstep and interstride trunk acceleration variability along different axes may indicate either adaptability or impairment [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on human movement with accelerometers shows that humans minimize head accelerations in order to allow visual and vestibular processes to function more efficiently [7]. These same processes work more efficiently in experienced riders; which gives them an advantage when jumping consecutive fences, since they are able to always take in spatial feedback to correct their position on the horse and to correct the horse's movements.…”
Section: Discussionmentioning
confidence: 99%